Integrated 16S rRNA sequencing and metagenomics insights into microbial dysbiosis and distinct virulence factors in inflammatory bowel disease - Wang, Haijing; Wang, Yuanjun; Yang, Libin; Feng, Jiawen; Tian, Shou; Chen, Lingyan; Huang, Wei; Liu, Jia; Wang, Xiaojin (Frontiers in Microbiology, 2024)
With the rapid pace of urbanization, there has been an observed increase in the prevalence and incidence of inflammatory bowel disease (IBD). In this context, a multicenter case-control study was conducted in a western city of China since the end of 2020, employing 16S rRNA and metagenomic sequencing to investigate the gut microbiota profiles of newly diagnosed IBD patients, including those with Crohn's disease (CD) and ulcerative colitis (UC), in comparison to healthy controls (n = 36 for 16S rRNA gene and n = 12 for metagenomics). Notably, the study found the phylum Proteobacteria, especially the genus Escherichia-Shigella, to be significantly elevated in CD patients, while the genus Enterococcus showed a marked increase in UC patients. In contrast, core gut microbiota such as the Christensenellaceae R-7 group, Fusicatenibacter, and Holdemanella were predominantly identified in healthy individuals. Furthermore, significant interactions between the microbiome and virulence factors were observed, and functional analysis indicated that oxidative stress might play a critical role in the pathological processes of IBD. These findings add valuable insights to the evolving conversation regarding the influence of gut microbiota on the pathogenesis of IBD across varied geographical populations, opening pathways for additional investigation.